Synthesis, stereochemistry and in vitro STD NMR and in silico HIV-1 PR enzyme-binding potential of MBH-derived inhibitors - Tukulula, Matshawandile; Olasupo, Idris A.; Mugumbate, Grace C.; Lobb, Kevin A.; Klein, Rosalyn; Sayed, Yasien; Tshiwawa, Tendamudzimu; Kaye, Perry T. (Elsevier, 2022)
Aza-Michael reactions of a pyridine-3-carbaldehyde-derived Morita-Baylis-Hillman (MBH) adduct with various amines have afforded a series of 10 diastereomeric products, stereochemical analysis of which has been achieved using a combination of NMR (1D, 2D and NOESY) and computer modelling methods. Saturation Transfer Difference (STD) 1H NMR spectroscopy and in silico molecular docking studies have been used to explore the HIV-1 protease sub-type C enzyme binding potential of these compounds in five different HIV-1 PR enzyme receptors.